Pengaruh Motivasi Intrinsik Komunikasi Verbal Kompensasi Finansial Terhadap Kinerja Individual Karyawan - Purnomo, Afif Joko; Prayekti, Prayekti; Herawati, Jajuk (Jurnal Ilmiah Manajemen Kesatuan, 2021)
ABSTRACT This study aims to examine whether the effect of intrinsic motivation, verbal communication, financial compensation, on individual employee performance. The research took place at the Department of Population and Civil Registration of Bantul Regency. The sampling method was nonprobability, and the sampling technique used purposive sampling. Data collection was carried out by means of a questionnaire which was directly submitted to the Department of Population and Civil Registration of Bantul Regency. The number of questionnaires that were processed was 48 questionnaires. Data were analyzed using SPSS 23 The results of the t-test research. has an influence on Employee Individual Performance (Y), Based on the results of data processing the Verbal Communication variable has a t-count smaller than t-table (1.024 <1.681) with a probability (0.312) greater than the significant level of 0.05, thus Communication Verbal (X2) partially has no effect on Employee Individual Performance (Y). 0.05, thus Financial Compensation (X3) partially has an effect on Individual Employee Performance (Y). And the f test can be seen that the calculated F value is 5.345 and the f table value is 1.681. The value of F count> F table and the sig value of 0.003 <0.05 (Î±) so that hypothesis 4 has a positive and significant effect on Intrinsic Motivation, Verbal Communication, Financial Compensation, on Kryawan's Individual Performance at the Department of Population and Civil Registration, Bantul Regency Key words: Influence of Intrinsic Motivation, Verbal Communication, Financial Compensation, Against Individual Employee Performance in the Department of Population and Civil Registration, Bantul Regency.